Someissues of defining the branch forming characteristics of international civil process (Journal of actual problems of jurisprudence, 2018)
In this article, authors analyze the issues of determining the branch forming signs of the domestic international civil process. In legal literature, the main and the only branch forming sign of lawsphere is the subject of legal regulation which is special, specific to only this legal relationship area. While studying an international civil process, the definition of its legal regulation subject has a problematic character, as in this branch of law a legal relationship is complicated with foreign elements. The authors analyze the existing views concerning the definition of the subject of international civil process.Key words: international civil process, branch of law, subject, legal relationship.